2012
DOI: 10.1111/1758-2229.12004
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale degrader community profiling over an aerobic/anaerobic redox gradient in a toluene‐contaminated aquifer

Abstract: Hydrocarbon contaminants in groundwater can be degraded by microbes under different redox settings, forming hot spots of degradation especially at the fringes of contaminant plumes. At a tar-oil-contaminated aquifer in Germany, it was previously shown that the distribution of anaerobic toluene degraders as traced via catabolic and ribosomal marker genes is highly correlated to zones of increased anaerobic degradation at the lower fringe of the plume. Here, we trace the respective distribution of aerobic toluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
4
25
0
1
Order By: Relevance
“…Earlier studies on sediments from the same sites showed a low variability within biological replicates and a high reproducibility of technical replicates with our T-RFLP protocol (Pilloni et al 2012). Moreover, key degrader populations identified match well with the findings from earlier studies (Winderl et al 2008, Anneser et al 2010, Larentis et al 2013). …”
Section: Sediment Elemental Compositionsupporting
confidence: 88%
See 4 more Smart Citations
“…Earlier studies on sediments from the same sites showed a low variability within biological replicates and a high reproducibility of technical replicates with our T-RFLP protocol (Pilloni et al 2012). Moreover, key degrader populations identified match well with the findings from earlier studies (Winderl et al 2008, Anneser et al 2010, Larentis et al 2013). …”
Section: Sediment Elemental Compositionsupporting
confidence: 88%
“…(T-RF 130 bp), Desulfobulbaceae (T-RF 159 bp), and Desulfosporosinus spp. (T-RF 228 bp), that have been identified in previous studies at this site (Winderl et al 2008, Anneser et al 2010, Pilloni et al 2011, Larentis et al 2013 were most abundant. Moreover, their relative abundance did not differ significantly between TQ and mica (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations